Changes over calendar time in the risk of specific first AIDS-defining events following HIV seroconversion, adjusting for competing risks. - Babiker, A; Darbyshire, J; Pezzotti, P; Porter, K; Rezza, G; Walker, SA; Beral, V; Coutinho, R; Del Amo, J; Gill, N; Lee, C; Meyer, L; et al. (2002)
BACKGROUND: Although studies have reported large reductions in the risks of AIDS and death since the introduction of potent anti-retroviral therapies, few have evaluated whether this has been similar for all AIDS-defining diseases. We wished to evaluate changes over time in the risk of specific AIDS-defining diseases, as first events, using data from individuals with known dates of HIV seroconversion. METHODS: Using a competing risks proportional hazards model on pooled data from 20 cohorts (CASCADE), we evaluated time from HIV seroconversion to each first AIDS-defining disease (16 groups) and to death without AIDS for four calendar periods, adjusting for exposure category, age, sex, acute infection, and stratifying by cohort. We compared results to those obtained from a cause-specific hazards model. RESULTS: Of 6,941, 2,021 (29%) developed AIDS and 437 (6%) died without AIDS. The risk of AIDS or death remained constant to 1996 then reduced; relative hazard = 0.89 (95% CI: 0.77-1.03); 0.90 (95% CI: 0.81-1.01); and 0.32 (95% CI: 0.28-0.37) for 1979-1990, 1991-1993, and 1997-2001, respectively, compared to 1994-1996. Significant risk reductions in 1997-2001 were observed in all but two AIDS-defining groups and death without AIDS in a competing risks model (with similar results from a cause-specific model). There was significant heterogeneity in the risk reduction across events; from 96% for cryptosporidiosis, to 17% for death without AIDS (P < 0.0001). CONCLUSION: These findings suggest that studies reporting a stable trend for particular AIDS diseases over the period 1979-2001 may not have accounted for the competing risks among other events or lack the power to detect smaller trends.